LOS PODCASTS EDUCATIVOS Y SU IMPACTO EN EL APRENDIZAJE DE ESTUDIANTES DE LA CARRERA DE COMUNICACIÓN UTB, PERIODO 2024. - KERLY BRIGGITTE SANTILLAN VILLAMAR (2024)
The present research project focuses on analyzing the impact of educational podcasts on the learning of students in the Communication program at the Technical University of Babahoyo during the 2024-A. For this reason, a descriptive-exploratory research design is used to understand the characteristics of the study population and to relate the existing variables within the addressed topic. This study has a qualitative-quantitative approach, employing questionnaires and observation sheets to understand the true impact of podcasts in the educational field. In this way, according to the results, it is know that the initiative comes from the program´s teachers, who, responding to the constant demands of technology, seek resources to offer a modern yet dynamic teaching approach.